"Estudio del ambiente organizacional en las empresas bananeras del Cantón Valencia Provincia de Los Ríos". - Mera Barros, Héctor Wladimir (2015)
This research was based on an analysis of the labor climate in the glass hacienda 2 situated in the grounds of the canton chipe Valencia province of Los Rios. Currently the company does not have a manual of procedures, code of conduct and a human resources department. Then we will present the findings in each study. • 44% of employees are between 5-10 years workers of glass ranch 2 and also 91% of employees have a contract indefinitely. • Among the main causes that affect the working environment in the crystal hacienda 2 are the lack of recognition of their work by their immediate superiors, overtime is not paid in full and also that the property does not provide adistramiento or informations about activities to be performed by employees. • Among the most viable solutions employees believe the creation of a human resources department and provide incentives for the achievements by employees With financial study was obtained that the project is feasible because the NPV is positive $ 507,156.08; IRR is 147% and the B / C ratio generate a profit of sixty cents for every dollar spent